Chronic Rhinosinusitis Related to Occupational Exposure: The Telemark Population Study. Issue 7 (July 2018) - Clarhed, Ulrika K.E.; Svendsen, Martin; Schiöler, Linus; Kongerud, Johny; Torén, Kjell; Hellgren, Johan; Fell, Anne Kristin
Abstract : Objective: The aim of this study was to investigate the association between occupational exposure and chronic rhinosinusitis. Methods: A random population from the region of Telemark, aged 16 to 50 years, answered a respiratory questionnaire including questions on chronic rhinosinusitis and exposure in the occupational environment. Results: A total of 16, 099/48, 142 subjects responded. The prevalence of chronic rhinosinusitis was 9%. Exposure associated with chronic rhinosinusitis comprised paper dust [odds ratio (OR) 1.3, 95% confidence interval (95% CI) 1.1 to 1.5], cleaning agents (OR 1.2, 95% CI 1.0 to 1.3), metal dust (OR 1.3, 95% CI 1.1 to 1.6), animals (OR 1.2, 95% CI 1.0 to 1.5), moisture/mould/mildew (OR 1.3, 95% CI 1.1 to 1.5), and physically strenuous work (OR 1.4, 95% CI 1.2 to 1.7). Conclusion: Occupational exposure to paper dust, cleaning agents, metal dust, animals, moisture/mould/mildew, and physically strenuous work was independently related to having chronic rhinosinusitis. An occupational history should be reviewed when assessing patients with chronic rhinosinusitis.